2016
DOI: 10.1002/lsm.22540
|View full text |Cite
|
Sign up to set email alerts
|

The histology of skin treated with a picosecond alexandrite laser and a fractional lens array

Abstract: These intra-epidermal cavities result from areas of laser-induced optical breakdown (LIOB). This injury is most consistent with a localized plasma formation in the epidermis initiated by the melanin absorption of the high energy picosecond light. It appears that treatments with this device and optic result in improvements in dyspigmentation and acne scars with new collagen, elastic tissue, and mucin. The production of this LIOB could directly stimulate an epidermal repair mechanism that results in these clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
199
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(209 citation statements)
references
References 8 publications
10
199
0
Order By: Relevance
“…At 1 week and later time points, microscopic epidermal necrotic debris, MEND, areas, consistent with previous histologic observation , were imaged across the treated epidermis, located mainly in the top layers, beneath the stratum corneum. The term MEND was initially used to describe damage associated with non‐ablative fractional resurfacing lasers but it can be applied as well to the damage observed with the fractioned picosecond devices .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…At 1 week and later time points, microscopic epidermal necrotic debris, MEND, areas, consistent with previous histologic observation , were imaged across the treated epidermis, located mainly in the top layers, beneath the stratum corneum. The term MEND was initially used to describe damage associated with non‐ablative fractional resurfacing lasers but it can be applied as well to the damage observed with the fractioned picosecond devices .…”
Section: Discussionsupporting
confidence: 84%
“…After 24 hours and at later time points, inflammatory cells were imaged in the proximity of damaged cells and MEND areas. In Tanghetti's recent study, histological findings indicated mild to moderate lymphocytic perivascular inflammation in the papillary dermis, but not in the epidermis .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…81 Microscopically, this modality leads to localized epidermal vacuoles with no collateral thermal damage, which then eventuates increased dermal collagen and elastin fibers. 82,83 Thus far, only a small number of studies have been conducted on these lasers. The PicoSure has been shown to improve the appearance and texture of atrophic facial acne scars, with similar efficacy to other fractional lasers.…”
Section: Picosecond Lasersmentioning
confidence: 99%
“…This allows an effective treatment at lower fluences, thereby decreasing the thermal energy transferred to surrounding tissues. In pigmented lesions, the mechanism of action is predominantly the fragmentation of melanosomes and the scattering of the melanin particles [36] . Friedman treated 29 melasma patients of skin types II-IV, who were unsuccessfully treated with topical agents, with a large spot 532-nm Nd:YAG picosecond-domain laser.…”
Section: Picosecond Lasersmentioning
confidence: 99%